Integrated Learning Models for Micro-Teaching Course - Blegur, Jusuf; Ma'mun, Amung; Berliana, .; Mahendra, Agus; Alif, Muhammad Nur; Juliantine, Tite; Lumba, Andreas J. F. (Ital Publication, 2024)
The progressive world of education needs to be accelerated by fulfilling the competencies of prospective teachers who are also progressive through a series of performance tasks that are relevant to learning needs in the 21st century. This research used Analysis, Design, Development, Implementation, and Evaluation (ADDIE) to innovate an integrated learning model for a micro-teaching course. A needs analysis was conducted on 75 students, two lecturers, and 30 teachers to assess actual performance, confirm desired performance, and identify causes of performance gaps. Researchers then designed performance tasks and validated them by 10 raters, tested them on 337 students to test the outer and inner models, and tested them on 30 students, 28 lecturers, and 49 teachers to test differences. Test content validity using the Aiken-V formula and test inter-rater reliability using ICC. Meanwhile, testing the validity and reliability of the construct uses outer and inner model analysis (CB-SEM), and the difference test uses ANOVA. The content validity results prove that all task performance meets the Aiken parameters (0.75-1.00), the interrater reliability value is 0.573, and the Cronbach alpha value is 0.931. Testing the outer model proves that the loading factor task performance value ranges from 0.709-0.874, the Cronbach alpha value ranges from 0.768-0.880, the composite reliability value ranges from 0.768-0.879, the AVE value ranges from 0.580-0.649, and the discriminant validity value ranges from 0.761-0.806. The inner model test proves that the Chi-Square/df value = 2.254, RMSEA value = 0.061, SRMR value = 0.036, NFI value = 0.910, TLI value = 0.936, and CFI value = 0.948. Meanwhile, the results of the ANOVA test confirm that the Sig value = 0.098, so it can be concluded that there are no significant differences between the three sample groups regarding the model innovation results. Thus, the 25-task performance in the integrated learning model has a significant psychometric function relative to the actual situation, so it becomes one of the references that lecturers can use to improve the competency of prospective teachers in micro-teaching courses (not limited to teaching skills, analytical thinking skills, academic integrity, and transformational leadership). Doi: 10.28991/ESJ-2024-08-06-020 Full Text: PDF